Selection of the Best Electronic Goods Supplier Using the MFEP Method - Ginting, Suranta Bill Patric; Manullang, Jontinus; Harmoko Lubis; Manik, Aditiarno (CV. Media Digital Publikasi Indonesia, 2023)
The selection of the best supplier to fulfil the needs of the store in the continuous sale of electronic goods requires a selectivity process using many factors, namely product quality, product price, service, and product delivery speed. However, the number of alternatives to be selected can make it difficult for decision makers to determine the best choice in the selection process. Therefore, a decision support system is needed to support decision making so that the selection of the best electronic goods supplier can be done easily and quickly. The decision-making method used to make accurate decision results on the decision support system for selecting the best supplier of electronic goods in this study is MFEP. The sample data used in this study consists of 6 (six) alternatives and 4 (four) criteria as a factor in determining alternative ranking results. In the final results of this study, it was concluded that the A4 alternative had the highest value (0.3758) compared to 5 (five) other alternatives, namely A6 (0.3544), A1 (0.3484), A3 (0.325), A2 (0.3136), and A5 (0.2828). So that alternative A4 is the most recommended alternative for decision makers to choose as a supplier of electronic goods.